2018
DOI: 10.1371/journal.pone.0207033
|View full text |Cite
|
Sign up to set email alerts
|

The imprint of microfibres in southern European deep seas

Abstract: Pollution of the marine environment by large and microscopic plastic fragments and their potential impacts on organisms has stimulated considerable research interest and has received widespread publicity. However, relatively little attention has been paid to the fate and effects of microplastic particles that are fibrous in shape, also referred as microfibres, which are mostly shed from synthetic textiles during production or washing. Here we assess composition and abundance of microfibres in seafloor sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
96
1
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(119 citation statements)
references
References 68 publications
14
96
1
8
Order By: Relevance
“…In a recent review, Gago et al (2018) suggested that fibers are more abundant than other shapes in seawater and sediments. Though this statement should be treated with caution as values obtained through very different methodologies were compared, fiber predominance is supported in our study area as separately reported for sediments (Sanchez-Vidal et al, 2018) and several pelagic and demersal fish species (Bellas et al, 2016;Compa et al, 2018;Nadal et al, 2016).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In a recent review, Gago et al (2018) suggested that fibers are more abundant than other shapes in seawater and sediments. Though this statement should be treated with caution as values obtained through very different methodologies were compared, fiber predominance is supported in our study area as separately reported for sediments (Sanchez-Vidal et al, 2018) and several pelagic and demersal fish species (Bellas et al, 2016;Compa et al, 2018;Nadal et al, 2016).…”
Section: Discussionsupporting
confidence: 78%
“…The great industrial activity and highly developed tourism, together with important fisheries and densely populated coastal segments might account for a great input of marine litter (Eriksen et al, 2014;Ramirez-Llodra et al, 2013). In the NW Mediterranean area, microplastic presence has been reported in surface waters (de Haan et al, 2019;Ruiz-Orejón et al, 2016;Schmidt et al, 2018), beaches (Constant et al, 2019), sediments (Sanchez-Vidal et al, 2018;Woodall et al, 2014) and several organisms, mainly coastal fish (Alomar and Deudero, 2017;Bellas et al, 2016;Collignon et al, 2012;Compa et al, 2018) but also in the deep-sea shrimp Aristeus antennatus (Carreras-Colom et al, 2018). In the latter, microplastic fibers might be retained for longer times compared to other organisms due to the presence of the gastric mill, a common food-grinding structure in decapods, which could hinder passage to the intestine (Watts et al, 2015;Cowie, 2016a, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…The duration of sediment storage in the onshore realm generally depends on the relief of the margin, which is related to the tectonic regime. Steep, tectonically active margins tend to have minimal onshore storage (e.g., Romans et al, 2016), and hence sediment and microplastics have a short residence time onshore; the opposite being true for mature, passive margins Woodall et al, 2014;Fischer et al, 2015;Bergmann et al, 2017;Graca et al, 2017;Leslie et al, 2017;Martin et al, 2017;Peng et al, 2018;Sanchez-Vidal et al, 2018;Kanhai et al, 2019). As a comparison data from marine litter distributions collected by Pham et al (2014) are shown.…”
Section: How Might Terrestrial Microplastics Be Introduced To Deep-sementioning
confidence: 99%
“…The potential environmental impacts of man-made plastic-derived microfibers (MFs) as a distinct component of MP pollution are increasingly of concern (De Falco et al, 2018;Henry et al, 2019;Sanchez-Vidal et al, 2018). It is estimated that every year, 0.19 million tonnes of synthetic MFs enter marine systems in discharge from wastewater treatment plants.…”
Section: Introductionmentioning
confidence: 99%
“…Although MF exposure has been observed in aquatic organisms (e.g. Mason et al, 2016;Sanchez-Vidal et al, 2018), and MFs have been detected in agricultural soils (Habib et al, 1998;Zubris and Richards, 2005;Zhang and Liu 2018;Zhang et al, 2019;Corradini et al, 2019), to date, investigation into MF effects on soil fauna and the potential MF-related ecotoxicological impacts is limited: for example, Song et al, (2019) exposed the land snail (Achatina fulica) to polyethylene terephthalate (PET) MFs and reported that MFs had adverse effects on feeding and fitness of the snails.…”
Section: Introductionmentioning
confidence: 99%